Coupled electromagnetic-thermal analysis of roadway inductive power transfer pads within a model pavement. (5th May 2021) - Amirpour, Maedeh; Kim, Seho; Battley, Matthew P.; Kelly, Piaras; Bickerton, Simon; Covic, Grant
Highlights: Multi-physics model to simulate a complex scenario of a high frequency IPT pad. Testing of an IPT pad in a roading structure under varying ambient temperatures. Simulation of continuous and periodic duty cycles. Abstract: Inductive Power Transfer (IPT) technology is a promising solution for wireless charging of Electric Vehicles (EVs). Given the expected uptake of IPT technology for both stationary and in motion in-road charging, many technical challenges regarding the electromagnetic field and thermal aspects need to be overcome to generate cost-effective and reliable solutions. One particular design constraint of in-road IPT systems is the occurrence of local increases in temperature during operation due to power losses in the wireless charging pads. In this paper, safe operating conditions of an enclosed wireless power transfer pad within a pavement model were identified. This aspect has been studied less rigorously compared with the electromagnetic design. This paper presents a numerical thermal analysis of a double-D (DD) prototype IPT primary pad based on two possible configurations; flush-mounted or buried, within a model pavement. A coupled electromagnetic-thermal simulation has been developed to aid in the development of thermally robust in-road IPT systems. In order to validate the proposed two-way coupled electromagnetic-thermal Finite Element (FE) simulations, experiments were performed to capture the evolving thermal field within an IPT primary pad under continuous and periodic duty cycles. This method made possible analysis of the heating patterns and so the identification of internal hotspots within an IPT pad in a roading structure. A thermal camera was used to provide detailed surface temperature distributions, while suitable application of non-metallic Fiber Bragg Grating (FBG) sensing technology enabled a robust technique to measure temperatures within the intense magnetic fields of a high frequency wireless power transfer system to be developed. Comparisons at steady state of the pavement surface temperature distribution, as well as point measurements with the pad and sand, demonstrate good accuracy. The maximum steady state surface temperature occurs at the centre of the sand surface where the IPT pad is placed and is approximately 87 °C and 100 °C for buried and flush-mounted pads, respectively. Moreover, for a 2/3 duty cycle loading, the maximum temperature of the pad tended to an average of approximately 76 °C, while at constant operation the average temperature is 105 °C. Therefore, a 5 min cooling period significantly reduced operating temperatures within the studied model IPT system. In the future, the methodologies proposed in this paper can also be used to improve the design of higher power IPT pads by identifying hotspots and maximum thermal stresses and determination of optimal charging patterns for heat dissipation.